In-Depth Analysis of the Role of the Acinetobactin Cluster in the Virulence of Acinetobacter baumannii - Conde-Pérez, Kelly; Vázquez-Ucha, Juan C.; Álvarez-Fraga, Laura; Ageitos, Lucía; Rumbo-Feal, Soraya; Martínez-Guitián, Marta; Trigo-Tasende, Noelia; Rodríguez, Jaime; Bou, Germán; Jiménez, Carlos; Beceiro, Alejandro; Poza, Margarita (Frontiers in Microbiology, 2021)
Acinetobacter baumannii is a multidrug-resistant pathogen that represents a serious threat to global health. A. baumannii possesses a wide range of virulence factors that contribute to the bacterial pathogenicity. Among them, the siderophore acinetobactin is one of the most important, being essential for the development of the infection. In this study we performed an in-depth analysis of the acinetobactin cluster in the strain A. baumannii ATCC 17978. For this purpose, nineteen individual isogenic mutant strains were generated, and further phenotypical analysis were performed. Individual mutants lacking the biosynthetic genes entA, basG, basC, basD and basB showed a significant loss in virulence, due to the disruption in the acinetobactin production. Similarly, the gene bauA, coding for the acinetobactin receptor, was also found to be crucial for the bacterial pathogenesis. In addition, the analysis of the ΔbasJ/ΔfbsB double mutant strain demonstrated the high level of genetic redundancy between siderophores where the role of specific genes of the acinetobactin cluster can be fulfilled by their fimsbactin redundant genes. Overall, this study highlights the essential role of entA, basG, basC, basD, basB and bauA in the pathogenicity of A. baumannii and provides potential therapeutic targets for the design of new antivirulence agents against this microorganism.